’À l’Amitié’: Henri Matisse et André Rouveyre - Caro, Fiona (Spunti e Ricerche, 2016)
The frequent exchange of letters between Henri Matisse, and André Rouveyre, when they were both isolated in the south of France during the Second World War, records detailed discussion about their work, as well as about their thoughts and anxieties during those war years. In particular, it gives an insight into the creation of one of Matisse’s most beautiful "livres de peintre," his Poèmes de Charles d’Orléans.